2021
DOI: 10.4081/ejtm.2021.9945
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of back muscles training and balance therapy in rehabilitation of patients with osteoporotic vertebral fractures

Abstract: Medical rehabilitation of patients with osteoporotic vertebral fractures (VF) remains an insufficiently developed topic and requires additional research. Aim of the study was to assess the efficiency of back muscles training and balance therapy in rehabilitation of patients with osteoporotic vertebral fractures. Prospective, interventional, open-label, controlled study in two parallel groups, performed in inpatient department settings at “National Medical Research Center of Rehabilitation and Balneology” durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…A tailored rehabilitation program based on balance and muscle strength tests has recently been proposed as an effective treatment option for basic motor function improvement and disability reduction [ 29 , 30 ]. A retrospective observational study found that compliance with a home exercise program was 62.86%, with several causes of non-compliance, including the absence of supervision by health personnel and a lack of motivation [ 31 ].…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…A tailored rehabilitation program based on balance and muscle strength tests has recently been proposed as an effective treatment option for basic motor function improvement and disability reduction [ 29 , 30 ]. A retrospective observational study found that compliance with a home exercise program was 62.86%, with several causes of non-compliance, including the absence of supervision by health personnel and a lack of motivation [ 31 ].…”
Section: Conservative Treatmentmentioning
confidence: 99%